ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN MAHASISWA TERHADAP PELAYANAN PERPUSTAKAAN UNIVERSITAS MUAHAMMADIYAH ACEH - Muhammad Yamin; Muhammad Zaini (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2011)
The aim of the study is to analyse factors impacting upon students satisfaction on Muhammadiyah Aceh University library services as there is a belief that different in satisfaction level did occur among students.             This study was performed at Muhammadiyah Aceh University library. Students satisfaction measured through five factors in service quality namely reliability, responsiveness, assurance, emphaty, and tangible. The population in the study is all 212 Muhammadiyah Aceh library registered-member students.  They are from six faculties and two academies within Muhammadiyah Aceh University. From those, 64 persons was sampled using stratified random sampling method.The result of the study shows that service quality positively associated with the students satisfaction on Muhammadiyah Aceh library services. The most positive association is between service quality and responsiveness. On the other hand, the least positive association is between service quality and reliability.